The Relationship between Self-Concept and Self-Adjustment in High School Students - Irfan, Witri Nengsi; Netrawati, Netrawati (Universitas Negeri Padang, 2023)
Self-adjustment is the process of how individuals achieve self-balance to meet needs according to their environment. One of the factors that influence self-adjustment is self-concept. This study aims to determine the relationship between self-concept and student self-adjustment at SMA Negeri 1 Guguak District. This research is a descriptive correlational research with quantitative methods. The total sample of 245 students was selected using the Simple Random Sampling technique. The instruments used were self-concept and self-adjustment questionnaires. The results showed that students at SMA Negeri 1 Guguak District had self-concept mostly in the high category with a percentage of 48.57%, and students' self-adjustment were in the high category with a percentage of 67.76%. The results of the correlation analysis show that there is a significant positive relationship between self-concept and self-adjustment of students at SMA Negeri 1 Guguak District with an r count of 0.526 with a significant level of 0.000. This means that the higher the student's self-concept, the higher the student's self-adjustment.